Differential expression of key enzymes of energy metabolism in preneoplastic and neoplastic rat liver lesions induced by N-nitrosomorpholine and dehydroepiandrosterone - Mayer, Doris; Metzger, Christel; Leonetti, Paola; Beier, Konstantin; Benner, Axel; Bannasch, Peter (International journal of cancer, 1998)
Preneoplastic liver foci and neoplasms of different morphological phenotypes were induced in rats with N-nitrosomorpholine (NNM; 120 mg/l in drinking water for 7 weeks) and the peroxisome proliferator dehydroepiandrosterone (DHEA; 0.6% in the diet for up to 84 weeks). Preneoplastic glycogen storage foci (GSF) occurred mainly upon treatment with NNM, and amphophilic cell foci (APF) were mainly observed in rats treated with DHEA alone or in combination with NNM. The 2 types of lesions belong to 2 different cellular lineages, the glycogenotic/basophilic lineage and the amphophilic lineage, which are characterized by distinct patterns of alterations in key enzymes of energy metabolism. Whereas in GSF enzymes of glucose metabolizing pathways were modified (increase in glucose-6-phosphate dehydrogenase and pyruvate kinase, decrease in glucose-6-phosphatase), APF mainly demonstrated alterations in mitochondrial enzymes (increase in cytochrome c oxidase, succinate dehydrogenase and glycerol-3-phosphate dehydrogenase) and, to a lower extent, in peroxisomal enzymes (increase in peroxisomal hydratase and acyl-CoA oxidase). The alterations in enzyme expression reflect an insulinomimetic effect in GSF and a thyromimetic effect in APF. Neoplasms resulting from APF show a more differentiated phenotype than those arising from GSF. We suggest that the different and in many aspects opposite effects of the 2 carcinogens on key enzymes of distinct pathways of energy metabolism modulate the process of neoplastic liver cell transformation and result in phenotypically different preneoplasias and neoplasias reflecting different cellular lineages. Int. J. Cancer (Pred. Oncol.): 79:232-240, 1998.© 1998 Wiley-Liss, Inc.